Barriers and Challenges in Implementing Green Management Practices: A Study of Corporate Implementation - Sapto Supriyanto; Thomas Chrityanto Matantu (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study explores the barriers and challenges organizations face when implementing green management practices. Through a qualitative approach involving in-depth interviews with 15 key informants and document analysis, the research reveals complex interconnections between organizational, resource-related, and external barriers that impede successful implementation. The findings highlight a "green management commitment paradox" where surface-level support for environmental initiatives, without corresponding structural changes, hinders implementation efforts. The study identifies three primary barrier categories: organizational resistance and leadership commitment issues, resource allocation challenges, and external regulatory pressures. The research contributes to both theory and practice by providing a nuanced understanding of how these barriers interact and influence implementation success. The findings suggest that organizations need to adopt a holistic approach to environmental management, considering both technical and social dimensions of change to achieve effective implementation of green management practices.